Effects of Pre-Meal Drinks with Protein and Amino Acids on Glycemic and Metabolic Responses at a Subsequent Composite Meal - Gunnerud, Ulrika J. (Public Library of Science, 2012)
BACKGROUND: Whey proteins have insulinogenic properties and the effect appears to originate from a specific postprandial plasma amino acid pattern. The insulinogenic effect can be mimicked by a specific mixture of the five amino acids iso, leu, lys, thr and val. OBJECTIVE: The objective was to evaluate the efficacy of pre-meal boluses of whey or soy protein with or without added amino acids on glycaemia, insulinemia as well as on plasma responses of incretins and amino acids at a subsequent composite meal. Additionally, plasma ghrelin and subjective appetite responses were studied. DESIGN: In randomized order, fourteen healthy volunteers were served a standardized composite ham sandwich meal with either water provided (250 ml) during the time course of the meal, or different pre-meal protein drinks (PMPD) (100 ml provided as a bolus) with additional water (150 ml) served to the meal. The PMPDs contained 9 g protein and were based on either whey or soy protein isolates, with or without addition of the five amino acids (iso, leu, lys, thr and val) or the five amino acids + arg. RESULTS: All PMPD meals significantly reduced incremental area for plasma glucose response (iAUC) during the first 60 min. All whey based PMPD meals displayed lower glycemic indices compared to the reference meal. There were no significant differences for the insulinemic indices. The early insulin response (iAUC 0–15 min) correlated positively to plasma amino acids, GIP and GLP-1 as well as to the glycemic profile. Additionally, inverse correlations were found between insulin iAUC 0–15 min and the glucose peak. CONCLUSION: The data suggests that a pre-meal drink containing specific proteins/amino acids significantly reduces postprandial glycemia following a composite meal, in absence of elevated insulinemic excursions. An early phase insulinemic response induced by plasma amino acids and incretins appears to mediate the effect. TRIAL REGISTRATION: ClinicalTrials.gov NCT01586780<NCT01586780>